2007
DOI: 10.1002/9780470175484
|View full text |Cite
|
Sign up to set email alerts
|

Biophysico‐Chemical Processes of Heavy Metals and Metalloids in Soil Environments

Abstract: Limit of Liability/Disclaimer of Warranty: While the publisher and author have used their best efforts in preparing this book, they make no representations or warranties with respect to the accuracy or completeness of the contents of this book and speciÞcally disclaim any implied warranties of merchantability or Þtness for a particular purpose. No warranty may be created or extended by sales representatives or written sales materials. The advice and strategies contained herein may not be suitable for your situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…It has been reported that electrostatic charge generated by radioactivity contributes significantly to surface interactions between particles and environmental surfaces [31]. In assessing the potential for interactions with complexing agents, uptake into the food chain and mobilization, paradoxically the same governing variables and processes affecting heavy metals and metalloids in the biosphere can be extrapolated to analogue radionuclides [32,33]. This leads to the discussion of sorption mechanisms:…”
Section: Sorption Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that electrostatic charge generated by radioactivity contributes significantly to surface interactions between particles and environmental surfaces [31]. In assessing the potential for interactions with complexing agents, uptake into the food chain and mobilization, paradoxically the same governing variables and processes affecting heavy metals and metalloids in the biosphere can be extrapolated to analogue radionuclides [32,33]. This leads to the discussion of sorption mechanisms:…”
Section: Sorption Mechanismsmentioning
confidence: 99%
“…The retardation factor, R and current decay coefficient, μ can be derived and is given by Eqs. (31) and (32), respectively [88,89]:…”
Section: Effects Of Sorption On Radionuclides Migrationmentioning
confidence: 99%